Pediatric Cataract Surgery: Comparison between Ages at Surgery and Contrast Sensitivity Outcomes - Aquirina Caesari Putri; Rozalina Loebis (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2017)
Background: Pediatric cataracts are major causes of children’s blindness. Surgery has proven to be beneficial in terms of visual function prognosis. Contrast sensitivity evaluation after surgery is as important as visual acuity considering that natural world consists of various objects in low-to-medium contrasts. The purpose of this study is to analyze the difference of contrast sensitivity outcomes based on ages at surgery. Method: Retrospective data of children with pediatric developmental cataract from July 2013 to November 2015 were collected. All children who underwent cataract surgery at 60-months-old or less were randomized into two groups, ≤24 months and >24-to-60 months. Contrast sensitivity was then examined with preferential-looking method using Hiding Heidi low-contrast test face chart. The main outcome measures were contrast sensitivity of both groups. Age-at-evaluation, cataract onset, duration of follow-up, duration of deprivation and visual acuity were also noted. Result: Of 14 children (23 eyes), 11 eyes (47,8%) were in ≤24 months group, 12eyes (52,2%) were in >24-to-60 months group. All eyes underwent cataract extraction and similar type of intraocular lens implantation. Mean age-at-surgery was 28,2 months±16,8 (SD). Mean contrast sensitivity for each group was 47,50 %±42,29 and 18,33%±27,38, respectively, with p-value 0,031. Further analysis of Spearman’s correlation test demonstrated significant negative correlation (rs = -0,559; p = 0,006) between the two groups. Conclusion: There was statistically significant difference in contrast sensitivity between those who underwent surgery at ≤24 months and >24-to-60 months. Children who underwent surgery at older ages tend to have better contrast sensitivity afterwards.